1996
DOI: 10.1042/bj3130373
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of human liver dihydrodiol dehydrogenases to hepatic bile-acid-binding protein and an oxidoreductase of human colon cells

Abstract: We previously isolated three monomeric dihydrodiol dehydrogenases, DD1, DD2 and DD4, from human liver, and cloned a cDNA (C9) thought to encode DD2, which is identical with those for human bile-acid-binding protein and an oxidoreductase of human colon carcinoma HT29 cells. In the present study we have provided evidence that the C9 cDNA clone encodes DD1, not DD2. A recombinant enzyme expressed from the cDNA in a bacterial system was purified, and its catalytic properties, bile-acid-binding ability and primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 21 publications
6
78
0
Order By: Relevance
“…Table 2 clearly shows that only 20a-HSD had the 20a-HSD activity, showing high kcat/Km values with their substrates, such as progesterone, 20a-OHP, pregnanolone and pregnandiol. This coincides with previous results (Hara et al 1996), which demonstrated that recombinant 20a-HSD shows an oxidation activity of 20a-OHP and pregnandiol, and their kinetic constants are similar to the values in Table 2. In addition to this, 20a-HSD had a weak PGE 2 9-ketoreductase activity to convert PGE 2 to PGF 2a .…”
Section: Substrate Speci®city Of Human 20a-hsd and Three Akrssupporting
confidence: 92%
See 3 more Smart Citations
“…Table 2 clearly shows that only 20a-HSD had the 20a-HSD activity, showing high kcat/Km values with their substrates, such as progesterone, 20a-OHP, pregnanolone and pregnandiol. This coincides with previous results (Hara et al 1996), which demonstrated that recombinant 20a-HSD shows an oxidation activity of 20a-OHP and pregnandiol, and their kinetic constants are similar to the values in Table 2. In addition to this, 20a-HSD had a weak PGE 2 9-ketoreductase activity to convert PGE 2 to PGF 2a .…”
Section: Substrate Speci®city Of Human 20a-hsd and Three Akrssupporting
confidence: 92%
“…Surprisingly, BABP did not have a 20a-HSD activity, and showed no or little enzymatic activities with the substrates, except for the synthetic substrates 1-acenaphthenol and (S)-( )-1-indanol. The activities to oxidize these synthetic substrates were inhibited by bile acids (data not shown), similarly to the previous report with BABP puri®ed from the liver (Hara et al 1996). On the other hand, PGFS shows prominent PGD 2 11-ketoreductase activity to reduce PGD 2 and to oxidize 9a, 11b-PGF 2 (Matsuura et al 1998;Suzuki-Yamamoto et al 1999).…”
Section: Substrate Speci®city Of Human 20a-hsd and Three Akrssupporting
confidence: 89%
See 2 more Smart Citations
“…Indomethacin methyl ester, which could only be tested up to 20 μM because its UV absorbance interfered with the assay at higher concentrations, effectively inhibited only AKR1C3 and had no effect on PQ reduction by the other AKR1C enzymes at the concentrations tested. Previously, Matsuura et al [10] had shown that indomethacin had high affinity for AKR1C3, while Hara et al [26] showed that indomethacin was a relatively weak inhibitor of AKR1C1 and AKR1C2. However, these studies used widely varied concentrations of substrate relative to the K M of the respective enzymes, making the results difficult to compare across isoform.…”
Section: Inhibition Of Akr1c-mediated Pq Reduction By Nsaids and Indomentioning
confidence: 99%